Exploring The Students' Grammatical Errors In Speaking English - Paulus Sainyakit (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This research aims to reveal the types of grammatical and the causes of errors made by the students in speaking performances in first-year students from Terang Bangsa University. It is necessary to identify, classify and describe the grammatical errors in order to build the students’ awareness in using english strucres and rules. This research used qualitative descriptive. The results of this research shown there were five types of grammatical errors in their speaking performances such as Omission, Overgeneralization, Misformation, Misordering and Addition. The most common errors were made by the students were The error in Omission that got the highest value which was 192 errors (57,8%) and it was caused by the first language and carelessness of the students. Next is Over-Generalization that got 63 errors (18,98%) caused by the students’ first language and overgeneralization. Then, followed by Misordering that got 31 errors (9,35%) caused by carelessness and the students’ first language and last is Addition and Misformation that got the same number of errors which were 23 errors (6,93%). The errors made by the students were caused by the intralingual error such as omission, overgeneralization and misformation in the category of verb, noun, conjunction, pronoun and preposition. In addition, the interlingual errors were misordering and addition. They were errors of overuse of preposition and incorrect word order, which based on their first language transfer. It is suggested that The teachers should use this result in order to develop a program to improve the students’ grammar skills in varies aspects. Teachers should also provide the environment so that the students might feel comfortable to speak English in the classroom.